THE ANALYSIS OF THE PRIVATE GREEN OPEN SPACE REQUIREMENTS IN KUPANG CITY: (Case Study at The Area of Hatta to Sudirman Street) - Pawiro, Surya A.; Fanggidae, Linda W; Messakh, Jakobis J. (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2024)
Increasing population and development will decrease land availability, specifically green open space. This phenomenon is also seen in the Hatta Street to Sudirman Street area, one of the critical arterial roads in Kupang City. In this highly developed area, there has been a decrease in the green open space area, possibly the driver of the decrease in the thermal comfort level. This study aims to determine the condition of the existing private green open space in the research location and to analyze its adequacy to the requirement. The objectives of this study are to (a) describe the conditions of the private green open space, (b) analyze the level of thermal comfort of residents, and (c) analyze the requirement for private green open space based on Oxygen (O₂) requirement. The method of this study is quantitative descriptive with data collection techniques through survey and descriptive data analysis. This study found that the thermal comfort in the study area can be categorized as "uncomfortable". It also concludes that there is a shortage of private green open space. The green open space requirement is 15.84% of the total area (5.29 Ha), while the existing green open space is only 2.73 Ha or 0.5% of the entire study area, which means there is a shortage of 2.56 hectares. This deficiency would worsen as the human and vehicle population increase over time. By 2030, the requirement for private green open space will be estimated to increase to 6.42 Ha.